ABDULLAH KADIRI - THE GENIUS OF THE XX CENTURY (Scientific journal of the Fergana State University, 2023)
The article explores the personality and creativity of the great Uzbek thinker and writer Abdulli Kadiri as a genius of the twentieth century; an attempt is also made to substantiate the natural genetic, socio-cultural, historical and political prerequisites for the formation of the thinker's personality as a genius. Also, the analysis of the phenomenon of "genius" is the central part of the article.